Constitutional courts as positive legislators : a comparative law study - Brewer Carías, Allan-Randolph (Cambridge University Press, 2011)
"This book analyzes the role of constitutional courts, conditioned by the principles of progressiveness and of prevalence of human rights, particularly regarding the important rediscovery of the right to equality and non-discrimination"--